2017
DOI: 10.1111/hdi.12607
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous perirenal hemorrhage in hemodialysis patient treated with selective embolization: A case series and review of the literature

Abstract: We are aware that HD patients have elevated risk of bleeding related complications, additionally the presence of an acute abdominal pain increases the suspicion of SPH as a possible cause. ACKD can be considered one of the possible risk factors for SPH in long-term HD patients. Interventional treatment for kidney injury is useful and safe for active bleeding in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…26 It is known that patients with chronic kidney disease who undergo haemodialysis have a predisposition to platelet dysfunction and bleeding secondary to endothelial abnormalities. 27,28 Among our cases, WS developed due to coagulopathy in one patient after coronary angiography and in another patient that was receiving haemodialysis.…”
Section: Discussionmentioning
confidence: 78%
“…26 It is known that patients with chronic kidney disease who undergo haemodialysis have a predisposition to platelet dysfunction and bleeding secondary to endothelial abnormalities. 27,28 Among our cases, WS developed due to coagulopathy in one patient after coronary angiography and in another patient that was receiving haemodialysis.…”
Section: Discussionmentioning
confidence: 78%
“…While patient vital signs are paramount, the diagnosis of SRH cannot be made in the absence of imaging and the presence of active extravasation on CT should also guide initial management. If the patient presents with unstable vital signs or active extravasation on imaging then angiogram with embolization is indicated after appropriate stabilization [ 9 - 10 ]. Overnight observation with conservative management, or even outpatient management with close clinical follow-up, may be appropriate if vital signs are stable and no active extravasation is observed on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Selective arterial embolization is another method to control active bleeding, particularly in hemodynamically unstable patients [8]. Many authors recommend embolization as the definitive therapy given strong evidence supporting its efficacy in cases of both traumatic and non-traumatic renal hemorrhage and relatively low-risk profile [6,[9][10][11]. However, some authors still consider embolization as a temporizing measure and second line to nephrectomy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous perirenal hemorrhage is a less frequent yet very important symptom of RCC. A study by Zhang et al showed that for >50% of patients with unclear causes of perirenal hematoma, an asymptomatic renal tumor will be identified, most often AML or RCC [ 23 , 24 ]. Performing a CT after a few months helps establishing a definitive diagnosis.…”
Section: Semiology and Natural Evolution Of Rccsmentioning
confidence: 99%